Atypical anorexia nervosa after bariatric surgery and the DSM‐5 diagnostic criteria: Commentary on Walsh et al. (2023). Issue 4 (2nd February 2023) - Conceição, Eva; Hilbert, Anja
Abstract: The applicability of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5) criteria for anorexia nervosa (AN) and atypical AN to individuals having undergone bariatric surgery poses several challenges due to the atypical presentation of AN‐like symptoms in this population. We describe these challenges, propose modifications to the corresponding diagnostic criteria, and delineate areas of research to inform possible adaptations of atypical AN criteria with applicability to postbariatric surgery populations. We discuss the utility of a strict definition of "significantly low weight" and "significant weight loss" as part of DSM‐5 Criterion A for AN and atypical AN, highlighting the importance of clinical judgment. We also question the clinical distinction between AN and atypical AN based solely on weight and argue that the hallmark feature of both diagnoses in postbariatric surgery populations should be persistent energy intake restriction coupled with persistent weight‐control behaviors. Finally, criteria B and C need to allow the distinction between common concerns of bariatric surgery patients regarding weight and eating, and clinically relevant symptoms of atypical AN and AN. Knowing the rates, the specificities, and the impact of atypical AN on postsurgical weight loss has important implications for the clinical attention of these often‐overlooked patients.